Confidence with Adele Bradley (Assemble You, 2023)
In today's episode, Adam talks to confidence guru Adele Bradley. Adele has been in the organisational development and people transformation world for a while, both for large companies and as a consultant. As a coach, Adele began to notice regular patterns with her clients. Specifically, low self-belief, low self-confidence, and low self-esteem. She has taken her experience and developed a formula for confidence, and that's what we discuss in today's session. You're are in for a real treat with this episode. Adele speaks from the heart, and lays out a formula to help you achieve a more confident outlook on life. Her book, Equation to Confidence is in the works, and provides a playbook to help you develop this crucial characteristic.